Identification of Cold-Hardy Zoysiagrass Genotypes for Tees and Greens in the Upper Transition Zone - Manoj Chhetri; Jack Fry; Megan Kennelly (Kansas Agricultural Experiment Station Research Reports, 2020)
Since the summer of 2017, 1,376 experimental zoysiagrass genotypes have been evaluated for winter survival in Olathe, KS, in an attempt to identify high quality, fine-textured types that survive in Kansas. After planting 458 progeny in the field in August 2017, only 17 experimental progeny survived when evaluated in spring 2018 (4%). In 2018, those 17 survivors were included with a new planting of 918 experimental progeny. In spring 2019, it was determined that 70 genotypes survived (8%). The 70 surviving progeny were transferred to a new, adjacent plot area in June 2019 and they varied in leaf texture (3.0 to 7.5 on a 1 to 9 scale; 9 = finest) and vigor (2.0 to 8.0 on a 1 to 9 scale; 9 = most vigorous) when visually rated on September 27, 2019. In 2020, all 70 progeny survived and showed variation in spring greenup in April (1.0 to 5.0; 1 to 9 scale, 9 = completely green). By early summer of 2020, best performing progeny with superior cold-hardiness and quality will be propagated for evaluation in larger plots starting in 2021.
Keywords: Fine-textured zoysiagrass